The factors that influencing that customer satisfaction towards shopping center in Kelantan: a case in KB Mall. - Afiqah Suhailah Mat Samsudin, (2012)
Customer satisfaction as a state of mind in which the customer’s needs, wants, and expectations throughout the product of service life haven been met or exceeded, resulting in future repurchase and loyalty. Customer satisfaction is important for any shopping center such as KB Mall because without customers support, the shopping center will difficult to expand from day to day in business world. The main purpose of this study was to identify the factors that influencing customer satisfaction towards shopping in Kelantan : A Case in KB Mall. The respondents involved in this study involving 120 people consisting of customers that had visited KB Mall now and before. The respondents were randomly selected. The instrument used to obtain information is through the questionnaire. Data were analyzed using SPSS version 18.0 to obtain the frequencies and percentages.